Gamification and serious games: A literature meta-analysis and integrative model - Baptista, Gonçalo; Oliveira, Tiago (Computers in human behavior, 2019)
In recent years we have witnessed a growing number of companies and institutions embedding game mechanics and game design techniques in all types of information systems, applications, and services. Following this trend, it is possible to find an increasing number of publications studying these subjects. With this meta-analysis we synthesise and integrate all the earlier literature and information available on gamification and serious games, assessing the current state-of-the-art in the field, filling a literature gap on this subject. We calculated meta-analysis effects from a total of 54 studies and 59 datasets collected from the literature. Attitude, enjoyment, and usefulness are the most relevant predictors of intention to use gamification. Intention, enjoyment, and usefulness are the most relevant predictors of the brand attitude towards gamification. Our results allow us to present a theoretical model that will be of value to future gamification studies. •The research process on gamification is getting more complex and time-consuming.•It's important to synthesise findings from existing research and knowledge.•A weight and meta-analysis was used to identify the most important constructs.•Usefulness and hedonic value are important predictors of intention to use.•A theoretical model based on the results is presented.